The Maoist Insurgency and the Cessation of Bhume Puja Among the Magars of Barkhu in West Rukum (Shodhmala शोधमाला, 2026)
This paper examines the steady decline of indigenous, religion-based socio-cultural practices within the Magar population in Aathbiskot Municipality in West Rukum, influenced by the interplay of armed conflict, urbanization, migration, social mobility, and increasing literacy. Bhume Puja, an earth-worship ritual that is based on real relationships with nature, lies at the heart of the discussion. This epistemology manifests through language, ritual practice, deities, and community-oriented problem-solving, forming a comprehensive framework for perceiving and interacting with the environment. But these kinds of cultural institutions at the grassroots level are dying more and more, frequently without anyone noticing at the individual, family, or community level. The Maoist insurgency that lasted from 1996 to 2006 was a major force behind the changes in rural Nepal's social and cultural landscape. In places like Barkhu in West Rukum, the conflict period saw a steep drop in group ritual observances, especially Bhume Puja. This sped up processes of cultural attrition that were already happening and made it harder for information to be passed down from one generation to the next. The article contends that indigenous scholars play an essential role in involving local practitioners and activists via critical dialogue, knowledge exchange, and archival initiatives, while also partnering with local governments to enhance heritage awareness and obtain financial and legislative backing for the preservation of these diminishing cultural and religious traditions.